Seawater Desalination Based on a Bubbling and Vacuum-Enhanced Direct Contact Membrane Distillation - Guangfu Cao; Qingfen Ma; Jingru Li; Shenghui Wang; Chengpeng Wang; Hui Lu; Yun Zheng (International Journal of Chemical Engineering)
A Bubbling and Vacuum-enhanced direct contact membrane distillation (BVDCMD) is proposed to improve the water production rate of the direct contact membrane distillation (DCMD-)based seawater desalination process. Its heat and mass transfer mechanism are theoretically analyzed, and a CFD model is established, which is verified by the published data. Four types of the noncondensable gas, “O2,” “air,” “N2,” and “H2,” are adopted as the bubbling gas, and their process enhancements under different pressure of permeate side, temperature, and NaCl concentration of feed side and flow velocities are investigated. The results show that the permeate flux increased remarkably with the decrease in the viscosity of the bubbling gas, and hence, “H2” is the best option for the bubbling gas, with the permeate flux being enhanced by 144.11% and the effective heat consumption being increased by 20.81% on average. The effective water production rate of BVDCMD is predicted to be 42.38% more than that of DCMD, proving its feasibility in the seawater desalination.